2017
DOI: 10.1371/journal.pone.0176269
|View full text |Cite
|
Sign up to set email alerts
|

Colonization behaviors of mountain pine beetle on novel hosts: Implications for range expansion into northeastern North America

Abstract: As climates change, thermal limits may no longer constrain some native herbivores within their historical ranges. The mountain pine beetle, Dendroctonus ponderosae Hopkins, is a tree-killing bark beetle native to western North America that is currently expanding its range. Continued eastward expansion through the newly invaded and novel jack pine (Pinus banksiana Lamb.) trees of the Canadian boreal forest could result in exposure of several species of novel potential host pines common in northeastern North Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…For each of the above nations, potential invasion pathways are different yet can be clearly illuminated. Countries such as India and Bangladesh border B. longissima ‐affected nations and may thus be subject to natural dispersal of the pest, possibly aided by increased climatic variability . Invasion risk in countries such as Brazil or Mexico, however, will depend on long‐distance trade of live palms, a well‐recognized driver of tree‐killing pest invasions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each of the above nations, potential invasion pathways are different yet can be clearly illuminated. Countries such as India and Bangladesh border B. longissima ‐affected nations and may thus be subject to natural dispersal of the pest, possibly aided by increased climatic variability . Invasion risk in countries such as Brazil or Mexico, however, will depend on long‐distance trade of live palms, a well‐recognized driver of tree‐killing pest invasions .…”
Section: Discussionmentioning
confidence: 99%
“…Countries such as India and Bangladesh border B. longissima-affected nations and may thus be subject to natural dispersal of the pest, possibly aided by increased climatic variability. 42 Invasion risk in countries such as Brazil or Mexico, however, will depend on long-distance trade of live palms, a well-recognized driver of tree-killing pest invasions. 43 Such a threat can only be counteracted by upgrading country-specific regulations for live plant imports and tightening quarantine and biosecurity measures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work (Furniss & Schenk, 1969;Rosenberger, Venette, Maddox, et al, 2017) has shown that mountain pine beetle will attack congeneric host material, despite substantial phylogenetic distances from historical hosts (e.g. red and Scots vs. ponderosa and lodgepole pine) and a lack of shared co-evolutionary history (Bertheau et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…All trees were c. 24 cm diameter at breast height (DBH, c. 1.3 m above ground) and free of visible signs of insect or disease. In 2013 and 2014, logs of common north eastern pines, jack, red, eastern white, and Scots pines were obtained from the Cloquet Forest Research Center, MN (Rosenberger, Venette, Maddox, & Aukema, 2017). The historical hosts, lodgepole and ponderosa pine, were obtained from the Big Horn Mountains in Wyoming and Black Hills in South Dakota respectively (Rosenberger, Venette, Maddox, et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation